2010
DOI: 10.1002/cncr.25506
|View full text |Cite
|
Sign up to set email alerts
|

Stability of estrogen receptor status in breast carcinoma

Abstract: BACKGROUND:The purposes of this study were to address a persistent controversy as to whether the ER status of a primary tumor remains stable during progression to metastasis and to evaluate the influence of disease course and prior systemic therapy on ER status. METHODS: Breast carcinomas from 227 women with known ER status in both primary tumor and paired metastasis were retrospectively reviewed. ER status was compared between primary and metastatic tumors with respect to metastatic site, interval between two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 50 publications
(63 reference statements)
2
17
0
2
Order By: Relevance
“…A switch of ERα and PR (29% each) was within the wide range of conversions reported earlier for other sites of relapse [8-11,26,27]. …”
Section: Discussionsupporting
confidence: 82%
“…A switch of ERα and PR (29% each) was within the wide range of conversions reported earlier for other sites of relapse [8-11,26,27]. …”
Section: Discussionsupporting
confidence: 82%
“…As negative ER and PR status has been determined to be a strong predictor of poor prognosis [4951], these results suggested that TAP2 and ER/PR status might be two independent indicators of breast cancer prognosis and function in independent mechanisms. Recent studies have shown some degrees of discordance in ER and PR status between primary and metastatic lesions [52,53]. In fact, in brain metastases, there were no associations between the TAP2 expression levels and ER/PR status, likely supporting our notion that these are two independent factors.…”
Section: Discussionsupporting
confidence: 65%
“…Almost half of patients with advanced disease do not respond to the drug and almost all patients with metastatic disease eventually develop resistance to it [3,4]. Intriguingly, the majority of patients who have relapsed on tamoxifen treatment retain ERα expression [5,6]. Several preclinical studies targeting ERα in tamoxifen-resistant cancers have yielded promising results [7][8][9].…”
Section: Introductionmentioning
confidence: 99%